Kajian Awal Penyusunan Algoritma Perhitungan Luas Tanah dan Faktor Koreksi dengan Metode Poligon Terbuka dan Tertutup - M. J. Andries (Universitas Bunda Mulia, 2017)
Data for land squares area and land volumes are strongly needed for private company neither is the government. Nowadays, the calculations of land squares are done manually, which need long and repetitive calculations. It is unfortunately risky for the researches. On the other side, none of the standard methods is used to calculate the volume of land burying. One of the alternatives when we intend to minimize the error of the calculation and measurement process is to integrate the step of calculation and measurement processes themselves. The underlined means to practice the automation on the recitation of several measurement output, and then the calculation of land squares, contour drawing, and land volumes can automatically be done. On the calculation of area squares, contour drawing, and land volumes, data of the measurements are put into calculation algorithm and are expected to be directly used in calculating the land squares, contour drawing, and land volumes, also automatically make the correction on the errors in order to minimize them. In this research, no hardware development is being developed. The author intended only to compose a calculation of algorithm to calculate land squares.Keywords: Land Squares, Algorithm, Integrate